CORONAVIRUS ANXIETY DAN PSYCHOLOGICAL DISTRESS PADA WARGA KAMPUNG LAMPION KOTA MALANG SELAMA MASA PANDEMI - Alhad, Muhammad Afif (JURNAL TALENTA PSIKOLOGI, 2022)
Coronavirus disease (Covid 19) has had a tremendous impact on people's lives in Indonesia. Adjusting conditions due to the pandemic is not only related to social and economic aspects, but also individual psychological conditions. This study was conducted with the aim of knowing the correlation between coronavirus anxiety and psychological distress of the residents of Kampung Lampion, Kelurahan Jodipan, Kota Malang. A total of 110 residents participated in this study. The instruments used were the Coronavirus Anxiety Scale and The Hopkins Symptoms Check List-25 (HSCL-25). The analysis used in this research was pearson correlation analysis. The results of the analysis showed that coronavirus anxiety variable has a significant correlation with psychological distress variable with a positive correlation coefficient which means that high coronavirus anxiety causes increased psychological distress and lower coronavirus anxiety causes decreased psychological distress experienced by residents of Kampung Lampion, Kelurahan Jodipan,Kota Malang.